Immune Responses to Gametocyte Antigens in a Malaria Endemic Population—The African falciparum Context: A Systematic Review and Meta-Analysis - Muthui, Michelle K.; Kamau, Alice; Bousema, Teun; Blagborough, Andrew M.; Bejon, Philip; Kapulu, Melissa C. (Frontiers in Immunology, 2019)
Background Malaria elimination remains a priority research agenda with the need for interventions that reduce and/or block malaria transmission from humans to mosquitoes. Transmission-blocking vaccines are in development, most of which target the transmission stage (i.e. gametocyte) antigens Pfs230 and Pfs48/45. For these interventions to be implemented, there is a need to understand the naturally acquired immunity to gametocytes. Several studies have measured the prevalence of immune responses to Pfs230 and Pfs48/45 in populations in malaria-endemic areas. Methods We conducted a systematic review of studies carried out in African populations that measured the prevalence of immune responses to the gametocyte antigens Pfs230 and Pfs48/45. We assessed seroprevalence of antibody responses to the two antigens and investigated the effects of covariates such as age, transmission intensity/endemicity, season and parasite prevalence on the prevalence of these antibody responses by meta-regression. Results We identified 12 studies covering 23 sites for inclusion in the analysis. We found that the range of reported seroprevalence to Pfs230 and Pfs48/45 varied widely across studies, from 0% to 64% for Pfs48/45 and from 6% to 72% for Pfs230. We also found a modest association between increased age and increased seroprevalence to Pfs230, adults were associated with higher seroprevalence estimates in comparison to children (β coefficient 0.21, 95% CI: 0.05 – 0.38, p = 0.042). Methodological factors were the most significant contributors to heterogeneity between studies which prevented calculation of pooled prevalence estimates. Conclusions Naturally acquired sexual stage immunity, as detected by antibodies to Pfs230 and Pfs48/45, was present in most studies analysed. Significant between-study heterogeneity was seen, and methodological factors were a major contributor to this, and prevented further analysis of epidemiological and biological factors. This demonstrates a need for standardised protocols for conducting and reporting seroepidemiological analyses.